(untitled) (Acta Entomologica Serbica, 2020)
Available geo-referenced data about the pine processionary moth (PPM) attacks in Stara Zagora province in Central Bulgaria were used to study the relationships between the frequency of attacks and soil conditions. It was established that the PPM prefers fresh, deep and fertile soils.